China's railway train speed, density and weight in developing. Issue 1 (3rd May 2022) - Jiang, Bo; Tian, Changhai; Deng, Jiehang; Zhu, Zitong
Abstract : Purpose: This study aims to analyze the development direction of train speed, density and weight in China. Design/methodology/approach: The development of China's railway in the past 40 years can be divided into 3 stages. At the stage of potential tapping and capacity expansion, it is important to improve the train weight and density by upgrading the existing lines, and improving transportation capacity rapidly. At the stage of railway speed increase, the first priority is to increase train speed, reduce the travel time of passenger train, and synchronously take into account the increase of train density and weight. At the stage of developing high-speed railway, train speed, density and weight are co-developing on demand. Findings: The train speed of high-speed railway will be 400 km h −1, the interval time of train tracking will be 3 min, and the traffic density will be more than 190 pairs per day. The running speed of high-speed freight EMU will reach 200 km h −1 and above. The maximum speed of passenger train on mixed passenger and freight railway can reach 200 km h −1 . The minimum interval time of train tracking can be compressed to 5 min. The freight train weight of 850 m series arrival-departure track railway can be increased to 4, 500–5, 000  t and that of 1, 050 m series to 5, 500–6, 400  t . EMU trains should gradually replace ordinary passenger trains to improve the quality of railway passenger service. Small formation trains will operate more in intercity railway, suburban railway and short-distance passenger transportation. Originality/value: The research can provide new connotations and requirements of railway train speed, density and weight in the new railway stage.